Poster 237: Distance Between the Tibial Physis and Meniscotibial Ligament: Implications for Meniscus Repair. Issue 7 (30th July 2022) - Tompkins, Marc; Yen, Yi-Meng; Karius, Alex; Cinque, Mark; Vuong, Brian; Ganley, Theodore; Wilson, Philip; Ellis, Henry; Green, Daniel; Fabricant, Peter; Boucher, Laura; Shea, Kevin; et al.
Objectives: Anatomic meniscus repair is frequently performed in young patients to maximize joint preservation and long-term joint health. Increasingly, surgeons are considering the role and function of the meniscotibial ligament structures during meniscus repair and transplant. The purpose of this study was to determine the distance between the tibial insertion of the meniscotibial ligament capsular attachment and the proximal tibial physis in skeletally immature subjects. Methods: 14 pediatric knee cadaver knee specimens (ages 3 months to 11 years) were dissected to clarify the relationship physis and meniscus/meniscotibial ligament complex. Metallic markers were placed marking the meniscotibial ligament capsular attachment in specific domains (Figure 1). The specimens underwent CT scanning to evaluate pin placement and relationship to the physis. OsiriX was used to measure the distances between the proximal tibial physis and the pins (placed at 5 points on both the lateral and medial meniscus- anterior root, 12 o'clock, 3/9 o'clock, 6 o'clock and posterior root). Specimens were divided into two groups for analysis- Group 1: ages 3 months- 2 years (10 pediatric knee specimens: 8 male, 2 female), and Group 2: ages 10-11 years (4 pediatric knee specimens: 2 male, 2 female). Results: There was an increase in the distance between the proximal tibial physis and the insertion points of the meniscotibial ligament with increasing specimen age. For both the medial and lateral menisci, Group 1's meniscotibial ligament insertion points were less than 10mm away from the physis. Group 2's meniscotibial ligament insertion points tended to be further away from the physis, but less than 20mm away, and sometimes even as close as <5mm (lateral posterior root). (Figure 2). Conclusions: This anatomic study defines the relationship between the physis and meniscotibial ligament capsular attachments that increases with age. These anatomic parameters can be considered as future meniscus repair and reconstruction techniques seek to restore the meniscus anatomy, stability, and mobility provided by the meniscotibial ligament structures. This anatomic information and may be used by surgeons to develop techniques to perform meniscal repair/reconstruction in patients that utilize the meniscotibial ligament structures. Avoiding direct physeal injury during menisco-tibial ligament repair is possible. Figure 1. Medial (blue) and lateral (red) Meniscal pin Placement. Figure 2. Distance (mm) from physis to Meniscotibial Ligament pins on Medial and Lateral Meniscus.